ElizaEdu: AI-powered Web3 System for Automated, Secure Event Attendance Verification in Educational Institutions - Nimje, Sarthak; Taneja, Rushab; Baviskar, Om; Patil, Rachana Yogesh (Journal of Trends in Computer Science and Smart Technology, 2025)
Educational institutions face significant challenges with event attendance verification, including manual document validation, fraud risks, and delayed approval processes. This study introduces ElizaEdu, a novel decentralized AI agent system utilizing Ethereum blockchain and ElizaOS to automate and secure attendance verification workflows for academic events. The proposed system integrates autonomous AI agents to handle document validation, approval processes, and ERP integration, while utilizing blockchain technology for immutable record-keeping. The system employs four specialized agents: RequestBot for initial verification, VerifyBot for teacher validation, ApproveBot for department head confirmation, and ERPBot for automatic attendance updates. Through a 3-month pilot implementation with 120 students and 15 faculty members, ElizaEdu demonstrated an 85% reduction in verification time, complete elimination of document fraud, and 84% decrease in administrative workload. The system achieves 97.3% accuracy in document validation and 100% data integrity through blockchain verification. This study presents the architecture, implementation details, and evaluation results, demonstrating ElizaEdu’s effectiveness in transforming attendance management in educational institutions.
Keywords: Blockchain; Ethereum; AI Agents; Educational ERP; Document Verification; Leave Management; Decentralized Systems; ElizaOS